The genesis of giants: behavioural ontogeny of male northern elephant seals. (August 2020) - Casey, C.; Charrier, I.; Mathevon, N.; Nasr, C.; Forman, P.; Reichmuth, C.
Abstract : Dominance hierarchies structure the adult social networks of many mammals. To identify the conditions that support the establishment of stable hierarchical relationships within groups of familiar rivals, we explored the ontogeny of spatial, social and communicative behaviour among male northern elephant seals, Mirounga angustirostris . We demonstrate that as male seals reach sexual maturity, they increase residency time ashore and restrict fine-scale movement patterns within the breeding colony. This spatiotemporal overlap creates a predictable social environment in which repeated interactions promote greater social connectivity between older individuals. Moreover, as males become physically and behaviourally mature, their ritualized vocal displays transition from highly variable calls to stable and unique individual acoustic signatures, supporting recognition between familiar competitors. The developmental onset of reliable signature calls – along with concurrent changes in space occupancy – coincide with the formation of stable, structured dominance relationships among top-level competitors. These findings advance our understanding of the ontogeny of social behaviour under conditions of extreme competition. Highlights: We explored spatial, social and communicative behaviour in male elephant seals. Subadults (<6 years) showed high variability in spatial, social and vocal behaviour. Adults had long residency times, small home ranges and familiar adult competitors. Adult vocal displays were stable and individually unique, facilitating recognition.